Transfer pricing in Serbia: Facing a sobering reality - Kostić Svetislav V. (Anali Pravnog Fakulteta u Beogradu)
This paper attempts to systematize the basic pillars of Serbian policy in the area of corporate income taxation of related party transactions (transfer pricing). The author looks at the very first Serbian transfer pricing legislation introduced in 1991 and follows its development through to the present. Principle focus is directed towards the policy drivers behind the 2012 and 2013 comprehensive reform of the Serbian transfer pricing provisions, which the author analyses with the added value of hindsight. Despite a generally positive view on what was achieved by the 2012 amendments to the Serbian transfer pricing legislation, the author offers a divergent view. A critical assessment is provided and the author stipulates the reasons which suggest that the respective amendments failed to meet desired goals in the area of transfer pricing set in 2012 and 2013. The author tries to deduce the lessons that should be taken into consideration in the future legislation reform initiatives and attempts to find alternative paths that should be taken in order to avoid repeating identical mistakes.